2016
DOI: 10.1073/pnas.1600587113
|View full text |Cite
|
Sign up to set email alerts
|

A viral kinase mimics S6 kinase to enhance cell proliferation

Abstract: Viruses depend upon the host cell for manufacturing components of progeny virions. To mitigate the inextricable dependence on host cell protein synthesis, viruses can modulate protein synthesis through a variety of mechanisms. We report that the viral protein kinase (vPK) encoded by open reading frame 36 (ORF36) of Kaposi's sarcoma-associated herpesvirus (KSHV) enhances protein synthesis by mimicking the function of the cellular protein S6 kinase (S6KB1). Similar to S6KB1, vPK phosphorylates the ribosomal S6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…We reported that vPK resembles and mimics the activity of the cellular ribosomal protein S6 kinase β-1 (S6KB1) (25). S6KB1 is downstream in the PI3K pathway and is phosphorylated by mTOR, a serine/threonine kinase that is part of several complexes within the PI3K pathway (33).…”
Section: Introduction Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We reported that vPK resembles and mimics the activity of the cellular ribosomal protein S6 kinase β-1 (S6KB1) (25). S6KB1 is downstream in the PI3K pathway and is phosphorylated by mTOR, a serine/threonine kinase that is part of several complexes within the PI3K pathway (33).…”
Section: Introduction Resultsmentioning
confidence: 99%
“…S6 is a component of the 40S ribosome subunit, and its phosphorylation is important for the ribosomal biogenesis transcriptional program (51). vPK phosphorylates S6, and increased phosphorylated S6 correlates with increased global protein synthesis, tubule formation, and anchorage-independent growth in cell culture (25). These data suggest that one potential mechanism by which vPK promotes tumorigenesis may be by its phosphorylation of S6.…”
Section: B Cells From Vpk Mice Lose Igm and Igd Expression Over Timementioning
confidence: 86%
See 3 more Smart Citations